Game theoretical mapping of causal interactions underlying visuo‐spatial attention in the human brain based on stroke lesions. Issue 7 (17th April 2017) - Toba, Monica N.; Zavaglia, Melissa; Rastelli, Federica; Valabrégue, Romain; Pradat‐Diehl, Pascale; Valero‐Cabré, Antoni; Hilgetag, Claus C.
Abstract: Anatomical studies conducted in neurological conditions have developed our understanding of the causal relationships between brain lesions and their clinical consequences. The analysis of lesion patterns extended across brain networks has been particularly useful in offering new insights on brain–behavior relationships. Here we applied multiperturbation Shapley value Analysis (MSA), a multivariate method based on coalitional game theory inferring causal regional contributions to specific behavioral outcomes from the characteristic functional deficits after stroke lesions. We established the causal patterns of contributions and interactions of nodes of the attentional orienting network on the basis of lesion and behavioral data from 25 right hemisphere stroke patients tested in visuo‐spatial attention tasks. We calculated the percentage of damaged voxels for five right hemisphere cortical regions contributing to attentional orienting, involving seven specific Brodmann Areas (BA): Frontal Eye Fields, (FEF‐BA6), Intraparietal Sulcus (IPS‐BA7), Inferior Frontal Gyrus (IFG‐BA44/BA45), Temporo‐Parietal Junction (TPJ‐BA39/BA40), and Inferior Occipital Gyrus (IOG‐BA19). We computed the MSA contributions of these seven BAs to three behavioral clinical tests (line bisection, bells cancellation, and letter cancelation). Our analyses indicated IPS as the main contributor to the attentional orienting and also revealed synergistic influences among IPS, TPJ, and IOG (for bells cancellation and line bisection) and between TPJ and IFG (for bells and letter cancellation tasks). The findings demonstrate the ability of the MSA approach to infer plausible causal contributions of relevant right hemisphere sites in poststroke visuo‐spatial attention and awareness disorders. Hum Brain Mapp 38:3454–3471, 2017 . ©2017 Wiley Periodicals, Inc.